What is the derivative of #f(t) = ((lnt)^2-t, tcsct ) #?
f'(t) =
f(t) = ( x(t), y(t0). f'(t) = ( x'(t), y'(t)).
By signing up, you agree to our Terms of Service and Privacy Policy
The derivative of ( f(t) = (\ln(t))^2 - t , \text{csc}(t) ) with respect to ( t ) is:
[ f'(t) = 2\ln(t)\cdot\frac{1}{t} - 1 \cdot \text{csc}(t) - t \cdot (-\text{csc}(t)\cdot\cot(t)) ]
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you differentiate the following parametric equation: # x(t)=cost, y(t)=sint #?
- How do you write #x = e^t-1# and #y=e^2t# as a cartesian equation and then sketch the curve?
- How do you differentiate the following parametric equation: # x(t)=(1-t)/e^t , y(t)=t/e^(3t) #?
- What is the derivative of #f(t) = (t^2+1 , e^(-t^2-t) ) #?
- How do you change the parametric equation to cartesian equation #x = t^2 - 1# and #y = t^3#?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7